Association of Atorvastatin with GDF9 and BMP15 Expression and in vitro Maturation of Mouse Oocytes: Atorvastatin GDF9 and BMP15 Expression and Mouse Oocytes - Sadeghi, Morteza; Chegini, Raziye; khafaei, Mostafa; Sabbagh ziarani, Fatemeh; Zafari, Fariba (Iranian Journal of Pharmaceutical Sciences, 2023)
Atorvastatin (ATV) is one of the hyperlipidemia treatment drugs with antioxidant and anti-inflammatory effects, growth differentiation factor 9 (GDF-9) and bone morphogenetic protein 15 (BMP-15) are two potent regulator factors of ovulation. This study investigated the effect of atorvastatin on GDF-9 and BMP-15 expression and explores its relationship with oocyte maturation in mice. A total of 200 oocytes from 40 mice were collected and divided into two groups (n=100 in each group), including the control group and the atorvastatin group (receiving 2 mg/kg atorvastatin). After oocyte culture in DMEM medium, GDF-9, and BMP-15 expression were evaluated by Real-time PCR. The rate of oocyte maturation was evaluated using fluorescent microscope scanning. Data were analyzed using an ANOVA test. GDF-9 and BMP-15 expression in control and atorvastatin groups were 2.3 and 4.8 (P≤0.05) and 1.2 and 3.4 fold respectively (P≤0.001). The oocyte maturation rate in the atorvastatin and control groups was 82% and 76%, respectively (p>0.05). According to our findings, low-dose atorvastatin caused overexpression of GDF-9 and BMP-15 in mice oocytes and it could improve the quality and maturation of mouse oocytes.